어머니의 스마트폰 과의존이 유아의 문제행동에 미치는 영향: 유아의 의도적 통제와 스마트폰 과의존의 이중매개효과 - 김나리(Na Ri Kim); 김정민(Jung Min Kim); 전정은(Jeong Eun Jeon) (Korean Journal of child studies, 2019)
Objectives: The purpose of this study is to evaluate the dual mediating effects of children’s effortful control and smartphone overdependence in the relation between mothers’ smartphone overdependence and children’s problem behaviors. Methods: The participants were 326 mothers with 3-to 5-year-old children, residing in Incheon. Data analyses were conducted using SPSS version 21.0 for descriptive statistics and PROCESS MACRO for the separate and dual mediating effect. Results: The major finding of the study was the statistically significant partial mediation effects of children’s effortful control and smartphone overdependence in the relation between mothers’ smartphone overdependence and children’s problem behaviors. Specifically, both the simple and the dual mediation effects of the mediators were found to be significant. Conclusion: The significance of this study is that it provides basis for specific interventions for children’s problem behaviors and finds influence of children’s effortful control. KCI Citation Count: 9